2020
DOI: 10.3389/fimmu.2020.568636
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophages Are Key Players in the Modulation of the Respiratory Antiviral Immunity Induced by Orally Administered Lacticaseibacillus rhamnosus CRL1505

Abstract: The oral administration of Lacticaseibacillus rhamnosus CRL1505 differentially modulates the respiratory innate antiviral immune response triggered by Toll-like receptor 3 (TLR3) activation in infant mice, improving the resistance to Respiratory Syncytial Virus (RSV) infection. In this work, by using macrophages depletion experiments and a detailed study of their production of cytokines and antiviral factors we clearly demonstrated the key role of this immune cell population in the impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 60 publications
(145 reference statements)
2
21
0
Order By: Relevance
“…The albumin content in BAL was quantified as an indicator of the increased permeability of the bronchoalveolar capillary barrier [ 21 ]. In addition, lactate dehydrogenase (LDH) activity was quantified as an indicator of general cytotoxicity [ 22 ]. Albumin content was determined colorimetrically using a diagnostic kit (Wiener Lab, Buenos Aires, Argentina) that is based on the binding of albumin to bromocresol green.…”
Section: Methodsmentioning
confidence: 99%
“…The albumin content in BAL was quantified as an indicator of the increased permeability of the bronchoalveolar capillary barrier [ 21 ]. In addition, lactate dehydrogenase (LDH) activity was quantified as an indicator of general cytotoxicity [ 22 ]. Albumin content was determined colorimetrically using a diagnostic kit (Wiener Lab, Buenos Aires, Argentina) that is based on the binding of albumin to bromocresol green.…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that immunobiotics with the ability of modulating the respiratory immunity are able to functionally modulate the alveolar macrophages response to viral challenges. In fact, our results indicate that alveolar macrophages greatly contribute to the augment of IFN-γ and IFN-β in the respiratory tract of mice orally treated with L. rhamnosus CRL1505 [ 115 ] or L. plantarum MPL16 (submitted for publication). Moreover, an improved expression of IFNAR1, Mx2, OAS1, OAS2, RNAseL and IFITM3 in alveolar macrophages after the oral treatment with L. rhamnosus CRL1505 or L. plantarum MPL16 was detected in our experiments.…”
Section: L Plantarum As Modulators Of Antiviral Immune Responses In Mucosal Tissuesmentioning
confidence: 99%
“…Not all lactobacilli strains possessing immunomodulatory abilities in the intestinal mucosa are capable of stimulating the respiratory immunity when orally administered [ 110 , 111 , 112 , 113 , 114 , 115 , 116 ]. Orally administered L. plantarum MPL16 but not L. plantarum CRL1506 was capable of modulating respiratory immunity.…”
Section: L Plantarum As Modulators Of Antiviral Immune Responses In Mucosal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations